BENDA ASING TELINGA HIDUNG TENGGOROK DI BAGIAN/SMF THT-KL BLU RSU PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI 2008 – DESEMBER 2011 - Sosir, Marthalisa S.; Palandeng, O. I.; Tumbel, R. E.C. (JURNAL BIOMEDIK : JBM, 2012)
Abstract: Sudden death, especially among children, can occur due to aspiration or the swallowing of foreign objects. Foreign objects in human organs are any kind of matter that comes from outside or inside the body, which normally is not present in these organs. This was a retrospective and descriptive  study and was aimed to determine the incidence of cases of foreign objects in the ear, nose, or throat found in the Ear, Nose, and Throat - Head and Neck Department, Faculty of Medicine, University of Sam Ratulangi, Manado, from January 2008 through December 2011 in which there were 482 cases. The results showed that the highest number of cases was in 2010 (163 cases, 33.81%), followed by 2009, 2011, and 2008. Male and female cases were 61.82% and 38.18% respectively. Cases in the age group 0-10 years were 218 (45.22%), followed by the age groups: >51 years, 41-50 years, 21-30 years, 31-40 years, and 11-20 years. The most usual anatomic locations of the foreign objects were the external auditory canal (58.29%), followed by the nose, pharynx, esophagus, larynx and bronchus. Successful extractions of the foreign objects occured in 99.17% cases. Conclusion: The highest number of cases was in 2010, being more frequent in males. The most vulnerable age group was 0-10 years, and the most usual anatomic location of the foreign objects was the external auditory canal. Successful extractions of foreign objects occured in almost all cases. Keywords: foreign objects, respiratory tract.     Abstrak: Kematian mendadak terutama pada anak-anak dapat terjadi akibat aspirasi atau tertelan benda asing. Benda asing dalam suatu organ tubuh ialah benda yang berasal dari luar atau dalam tubuh, yang dalam keadaan normal tidak terdapat dalam organ tersebut. Penelitian ini bersifat retrospektif – deskriptif dan bertujuan untuk  mengetahui insiden kasus benda asing telinga, hidung, dan tenggorok di Poliklinik THT-KL RSU Prof. Dr.R D Kandou Manado selang bulan Januari 2008- Desember 2011. Data kasus sebanyak 482 dikumpulkan secara retrospektif dari catatan medik. Jumlah  kasus tertinggi pada tahun 2010 (163 kasus, 33,81%), diikuti oleh 2009, 2011, dan 2008. Kasus laki-laki sebanyak 61,82% dan perempuan 38,18%. Kelompok usia 0-10 tahun sebanyak 218 kasus (45,22%), diikuti kelompok usia >51 tahun, 41-50 tahun, 21-30 tahun, 31-40 tahun, dan 11-20 tahun. Lokasi anatomi benda asing tersering pada meatus akustikus eksterna (58,29%), kemudian hidung, faring, esofagus, dan laring serta bronkus. Keberhasilan penatalaksanaan benda asing (ekstraksi) 99,17%. Simpulan: Kasus benda asing pada telinga, hidung dan tenggorok tertinggi pada tahun 2010 dengan kelompok usia 0-10 tahun, jenis kelamin laki-laki, dan lokasi benda asing tersering pada meatus akustikus eksterna dengan tingkat keberhasilan ekstraksi yang tinggi. Kata kunci: benda asing, saluran napas.